LITERATURE DEVELOPMENT OF E-COMMERCE AND SUPPLY CHAIN: BIBLIOMETRIC ANALYSIS - Witosari, Diana; Nisa', Atalia Dzuifatun; Widarjo, Wahyu (Universitas Muria Kudus, 2025)
The study of e-commerce and supply chain performance has experienced rapid development over the last few decades. This research analyzes the literature on the supply chain of e-commerce on a global scale and identifies interesting variables that researchers can further develop in future studies. The literature analyzed for this research consists of bibliometric data from 2014 to 2024. The bibliometric analysis was conducted using the Scopus database and analyzed with the software tool VOSviewer. The results indicate that research on supply chains and e-commerce has grown significantly over the past ten years. Additionally, new and intriguing variables for investigation have emerged, such as big data, agency selling, and live streaming. It is important to note that China has been a prominent focus in every aspect of the bibliometric analysis method used in this study. One limitation of this research is the lack of in-depth analysis, highlighting the need for further exploration using other research methods.